Factors related to open defecation behavior: A cross-sectional study in Serang City, Banten, Indonesia - Kurniatillah, Nia; Hayat, Fauzul; Masyruroh, Anis (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Open defecation remains a public health problem in Indonesia, contributing to various diseases such as diarrheal diseases within communities. Open defecation can be influenced by several factors, including socio-demographic, cultural, financial, and poor sanitation factors. However, these factors remain poorly investigated. Objective: This study aimed to determine the association between age, gender, level of education, knowledge, attitude, family income, local government support, availability of clean water, and family latrines with open defecation behavior in Serang City, Banten Province, Indonesia. Methods: A cross-sectional study design was selected, using purposive sampling in the study area. Data were collected from 220 respondents using a structured questionnaire from June to October 2022. Chi-square test was used to analyze the data. Results: The majority of the respondents were females (52.7%), and the dominant age group was >30 years old (50.9%). Bivariate analysis showed a significant relationship between gender (OR = 8.190, 95% CI =4 .460-15.038), attitude level (OR = 2.391, 95% CI = 1.271-4.500), family income (OR = 35.964, 95% CI = 8.477-152.582), local government support (OR = 4.540, 95% CI = 2.073-9.943), availability of clean water (OR = 2.834, 95% CI =1.632-4.922), and family latrines (OR = 19.260, 95% CI = 9.612-38.591) with open defecation behavior (p <0.05). There was no significant relationship between age, level of education, and knowledge with open defecation behavior (p >0.05). Conclusion: The main variables that significantly influenced open defecation behavior were female gender, family income, local government support, and family latrines. Therefore, there is a need for a policy shift to involve female empowerment and local government support to construct affordable and effective latrines, aiming to improve the current practice and eliminate open defecation.